Contamination in COVID-19 sample - the elaboration between medical and legal impact - Firmansyah, Yohanes; ., Ernawati; Gosal, Darren; Haryanto, Imam; ., Hendsun (International Journal of Advances in Medicine, 2021)
The impact of COVID-19 is enormous on various aspects of human life around the world, especially in the health system. The gold standard used to detect COVID-19 is nucleic acid amplification-based molecular testing. The fact in the field showed that this testing is prone to contamination, leading to misinterpretation and diagnosis. This error has the potential to have further legal implications. This study was a case report using a juridical-normative approach from various primary and secondary sources. A 26-year-old man has tested positive for COVID-19. After further investigation, it was found that there was a diagnosis error due to the contamination of the testing sample in the laboratory where the sample was examined. The contamination that occurs is not only the fault of health workers but is a series of impacts from problems in hospital regulations, the government, and the community’s components. This incident affects legal responsibility for health workers and medical consequences on the community. COVID-19 infection is not only closely related to medical problems but also closely related to social and legal issues. Whoever, especially health workers, will receive legal and social impacts other than hospitals, the government and the community from this incident.